1987
DOI: 10.1063/1.99001
|View full text |Cite
|
Sign up to set email alerts
|

Ablation and etching of polymethylmethacrylate by very short (160 fs) ultraviolet (308 nm) laser pulses

Abstract: Articles you may be interested inEnhancement of material ablation using 248, 308, 532, 1064 nm laser pulse with a water film on the treated surface Study of surface reflectivity and etch rates of polyimide (Kapton H) utilizing doublepulsed 308 nm laser radiation Cumulative effect near ablation threshold of polymer by 308nm excimer laser pulse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(68 citation statements)
references
References 7 publications
3
65
0
Order By: Relevance
“…Sapphire was chosen as a highly conductive material and PMMA as a low conductor. For the latter, the ablation threshold is high enough (900-1100 mJ/cm 2 [39,40]) to ensure that the substrate does not undergo ablation in the investigated fluence range.…”
Section: 3mentioning
confidence: 99%
“…Sapphire was chosen as a highly conductive material and PMMA as a low conductor. For the latter, the ablation threshold is high enough (900-1100 mJ/cm 2 [39,40]) to ensure that the substrate does not undergo ablation in the investigated fluence range.…”
Section: 3mentioning
confidence: 99%
“…The extension to laser nanomachining is a fascinating and relatively new field, where basic research and advanced applications have moved at the same pace since the first report in 1987 that ultrafast lasers are feasible for materials processing. The sharp ablation of polymethyl methacrylate was demonstrated, using a 160-femtosecond UV excimer laser [1]. Two impressive results were reported that, namely, a heat affected zone (HAZ) almost does not form in the irradiated target and that the ablation threshold is significantly lower than using a nanosecond excimer laser.…”
Section: Introductionmentioning
confidence: 79%
“…The situation is the same for other major conferences including the Conference on Laser Ablation (COLA) and the International Symposium on Laser Precision Microfabrication (LPM). Looking back at the history of ultrafast laser processing, it was initiated in 1987 by the Srinivasan [10] and Stuke groups [11]. Both of these groups demonstrated clean polymer ablation using femtosecond excimer lasers almost without the formation of an HAZ and with a significant reduction of the ablation threshold compared with nanosecond lasers.…”
Section: Introduction and Historymentioning
confidence: 99%
“…In addition, if the focus position of the ultrafast laser beam is set inside a transparent material, then multiphoton absorption can be confined to a region near the focal volume to implement internal modification and 3D micro-and nanofabrication of transparent materials [7][8][9]. Thus, since the first demonstration of femtosecond laser ablation in 1987 [10,11], research and development with regard to ultrafast laser processing has rapidly advanced. Figure 1 shows the evolution of the number of papers related to ultrafast laser processing presented at the SPIE LAMOM conference each year.…”
Section: Introduction and Historymentioning
confidence: 99%